Enhancing the Delivery of Library’s Services through the Implementation of An Emerging Information Technology: A Process Framework - Bahri, Shamshul (2010)
This paper presents a process framework for implementing an emerging information technology in library. The motivation for this framework came from the lack of such tool to managers in service organizations such as libraries that have been actively implementing emerging technologies to enhance the delivery of their services. To develop the framework, a study was conducted on the implementation of Radio Frequency Identification (RFID) by the first public library in the UK to adopt the technology. Using the Lewin’s model of change as the study’s theoretical framework and the grounded theory approach as the study’s research method, an implementation process framework of an emerging technology was developed. The contribution of the framework is twofold. First, the framework contributes towards the state-of-the-art knowledge on service sciences and emerging technology implementation. Second, it provides guidance to future managers in service organizations on how best to manage the implementation of an emerging technology.